Plant-Microbe Interactions - Gary Stacey; Noel T. Keen (New York International Thomson)
This book described the science and nature regularly must realize that the field of plant- microbe interaction to basic plant biology
Vector Genotype Whitefly
Keywords: Vector, Genotype, Whitefly